Randa Abdel-Fattah in conversation - Brioua, Nadira; Quayum, Mohammad Abdul (IIUM Press, International Islamic University Malaysia, 2018)
An interview with the Muslim Australian writer Randa Abdel-Fattah in which she discusses different aspects of her life and career, and explains why it is important for her to write and how her writing helps Muslim minorities in Australia, especially in the post-9/11 era.